2020
DOI: 10.14693/jdi.v27i1.1120
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health and Related Behavior of Children Aged 9–12 with Attention Deficit Hyperactivity Disorder in Tron District, Thailand

Abstract: Attention deficit hyperactivity disorder (ADHD) is a common biobehavioral childhood disorder that leads to significant behavioral problems that affect everyday life. Objective: This study aimed to compare oral health and oral health behaviors among children with and without ADHD. Methods: The study included 105 children aged 9-12 years with ADHD and 105 age-, gender-, and family income-matched children without ADHD. Clinical data as caries, periodontal health, and traumatic dental injuries were recorded by cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(38 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…The full texts of 23 were evaluated in phase 2. Thirteen studies fulfilled the eligibility criteria and were included in this systematic review and meta-analysis [Broadbent et al, 2004;Grooms et al, 2005;Blomqvist et al, 2007;Bimstein et al, 2008;Chandra et al, 2009;Blomqvist et al, 2011;Chau et al, 2017;Sabeti et al, 2017;Mota-Veloso et al, 2018a;Mota-Veloso et al, 2018b;Begnini et al, 2019;Ehlers et al, 2019;Khobkham et al, 2020]. One study was identified in Google Scholar [Sabeti et al, 2017].…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…The full texts of 23 were evaluated in phase 2. Thirteen studies fulfilled the eligibility criteria and were included in this systematic review and meta-analysis [Broadbent et al, 2004;Grooms et al, 2005;Blomqvist et al, 2007;Bimstein et al, 2008;Chandra et al, 2009;Blomqvist et al, 2011;Chau et al, 2017;Sabeti et al, 2017;Mota-Veloso et al, 2018a;Mota-Veloso et al, 2018b;Begnini et al, 2019;Ehlers et al, 2019;Khobkham et al, 2020]. One study was identified in Google Scholar [Sabeti et al, 2017].…”
Section: Study Selectionmentioning
confidence: 99%
“…Among the 13 included studies, 11 were cross-sectional studies with the control group [Grooms et al, 2005;Blomqvist et al, 2007;Bimstein et al, 2008;Chandra et al, 2009;Blomqvist et al, 2011;Chau et al, 2017;Sabeti et al, 2017;Mota-Veloso et al, 2018a;Begnini et al, 2019;Ehlers et al, 2019;Khobkham et al, 2020] and 2 were case-control studies [Broadbent et al, 2004;Mota-Veloso et al, 2018b]. All studies were published in English.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations